Metaphase cytogenetics and single nucleotide polymorphism arrays in myeloid malignancies - Fernanda Borges da Silva; Fabı́ola Traina (2015)
Chromosomal abnormalities provide useful diagnostic andprognostic information, and may also guide therapy inmyeloid malignancies, especially in myelodysplastic syn-dromes (MDS) and acute myeloid leukemia (AML). The revisedinternational prognostic score system for MDS highlights theimplication of chromosomal abnormalities on the prognosisof MDS patients.